Kitten and the night watchman - Sullivan, John (Writer of books for children); Yoo, Taeeun (New York : Simon & Schuster Books for Young Readers, 2020)
As he makes his rounds, a night watchman hears birds calling, insects buzzing, and vehicles roaring by, while a stray kitten keeps him company.
"A Paula Wiseman Book."
109558
Keywords: Watchmen -- Juvenile fiction; Cats -- Juvenile fiction; Animals; Sound; Picture books; Juvenile works; Picture books